Maternal wellbeing of Malaysian mothers after the birth of a preterm infant - Liz Jones; Jeevitha Mariapun; Abbey Xiao Qian Tan; Zaid Kassim; Tin Tin Su (BMC, 2023)
Abstract Background In Malaysia approximately 7% of births result in a preterm birth (< 37 weeks). Research in many other countries has found that mothers of preterm infants experience poorer psychological wellbeing. However, there has been limited research in Malaysia. We examined wellbeing, using the WHO Quality of Life brief version questionnaire (WHOQOL-BREF), in mothers who have preterm and full-term infants. Methods Data was collected as part of the South East Asian Community Observatory MISS-P project. A total of 3221 mothers (7.9% with a preterm and 92.1 with a full-term birth) completed a survey, with a range of measures, including the WHOQoL-BREF and sociodemographic questions. Results For the physical health, psychological wellbeing and quality of their environment WHOQOL-BREF domains, a lower gestational age, a lower education level, and having had an emergency caesarean delivery were significantly associated (p < 0.05) with a lower quality of life, and there was a weak effect for ethnicity for some domains. The effects were strongest for mothers' education level. Conclusions There is a weak but significant relationship between the gestational age of an infant and the mother's quality of life. Mothers in Malaysia with a preterm infant or a lower level of education may benefit from additional support.